Analisis Kebijakan Dividen Perusahaan dan Kebijakan Hutang (Studi Kasus Pada Sektor Industri Dasar dan Kimia di Bursa Efek Indonesia - Nurman; Romansyah Sahabuddin; Muh. Ichwan Musa; Arsil Ainun Rahman; Anwar (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the level of dividend policy analysis proxied by the Dividend Payout Ratio (DPR) and debt policy proxied by the Debt To Equity Ratio (DER). This study uses a sample of manufacturing companies in the basic and chemical industry sectors that are listed on the Indonesia Stock Exchange (IDX) for 2020-2021. The type of data used in this research is secondary data. Data analysis was performed by analyzing financial ratios, namely the Dividend Payout Ratio and the Debt To Equity Ratio. The results of this study indicate that: 1). Dividend policy in review from the ratio of market prospects as measured by the DPR's Dividend Payout Ratio, it can be seen that the company's ability to pay dividends is stable. Meanwhile 2). The company's debt policy in terms of the solvency ratio (Leverage/coverage) as measured by the Debt To Equity Ratio (DER) for 2020-2021 can be categorized as high with a low.